PEMESANAN JASA PRINT SECARA ONLINE BERBASIS WEB DAN APLIKASI ANDROID - Thamrin, Stella Nathania; Fat, Joni; Setyaningsih, Endah (TESLA: Jurnal Teknik Elektro, 2023)
The need to print file is needed by various service users among the academic community and general public. Currently, service users who want to print files need to queue at print service provider. Taking queue number, waiting to be called, inserting flashdisk into the print service provider’s computer will take a long time. If there are many people queuing at certain time, there can be congestion which is not in accordance with government's direction to implement physical distancing. There needs to be a solution that can benefit service users and providers, namely making website and Android application for ordering print services. Website and Android application for ordering print services are designed using CodeIgniter framework and AppsGeyser with user welcome page, registration page, login page, profile page, your order page, order page, cart page and log out page. Website and Android application aims to connect users and print service providers online. Service users can upload files and make payments through accounts or digital wallets. Service users only need to pick up the print at print service provider's place if they received notification to pick up order. Website and Android application for ordering print services successfully facilitate service users in ordering print services and making payments online. It presents the order status and order details containing total price, material, size, and quantity of order well. Availability of various features on website and Android application can be useful to minimize the density of service users at the location and reduce physical contact.